2014
DOI: 10.1016/j.jcin.2013.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Lumen Gain and Restoration of Pulsatility After Implantation of a Bioresorbable Vascular Scaffold in Porcine Coronary Arteries

Abstract: Starting at 12 months, BVS-implanted porcine coronary arteries underwent progressive lumen gain and showed restored pulsatility. These benefits demonstrated preclinically may translate into improvements in long-term clinical outcomes for patients treated with BVS compared with conventional drug-eluting stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 30 publications
0
26
0
2
Order By: Relevance
“…Recent 5-year follow-up results after Absorb implantation concluded that the mean lumen area tended to increase from 6 months to 1 year and 5 years [29] . Progressive lumen gain was also observed after Absorb implantation in porcine coronary arteries [30] , for which the lumen area kept stable up to 6 months and then showed a progressive increase from one to 3.5 years. These studies confirmed the lumen gain after scaffold implantation over the degradation times, especially from 6 months onwards.…”
Section: Degradation Behaviourmentioning
confidence: 73%
“…Recent 5-year follow-up results after Absorb implantation concluded that the mean lumen area tended to increase from 6 months to 1 year and 5 years [29] . Progressive lumen gain was also observed after Absorb implantation in porcine coronary arteries [30] , for which the lumen area kept stable up to 6 months and then showed a progressive increase from one to 3.5 years. These studies confirmed the lumen gain after scaffold implantation over the degradation times, especially from 6 months onwards.…”
Section: Degradation Behaviourmentioning
confidence: 73%
“…Lately, bioresorbable vascular scaffolds (BVS) are in the focus of interest. Interestingly, for both “metallic free” concepts of BVS and DCB-only angioplasty, late lumen enlargement has been shown, which is contrary to the well-known vessel response after POBA, BMS or DES implantation resulting always in late lumen loss [38, 39]. Also, restoration of vasomotion after angioplasty is advantageous and might maintain positive long-term outcomes including relief of angina symptoms [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…There are many potential advantages of using BVS in SCAD. BVS offers the theoretical advantage of restoration of native vessel vasomotion and adaptive shear stress allowing a process of late luminal enlargement and late expansive remodeling once the scaffold degraded [14]. Moreover, even if the radial strength of the device is still limited compared to a metal platform, it is probably enough to fix the intimal flap preventing a further expansion of the hematoma.…”
Section: Discussionmentioning
confidence: 99%